International initiatives in Agricultural R&D: The changing fortunes of the CGIAR - Alston, Julian M.; Dehmer, Steven; Pardey, Philip G. (International Food Policy Research Institute, 2006)
Many believe that agricultural productivity growth, driven by research-induced technical change, is essential to long-run economic development. Consequently, a strategy of agriculture-led development has been a critical element in aid and economic-development policy around the world since World War II. An important component of this strategy has been the progressive development of the system of international agricultural research centers (IARCs) known as the Consultative Group on International Agricultural Research (CGIAR, or CG for short), in conjunction with and as a complement to the national agricultural research systems (NARSs) in developing countries.